Effectiveness of virtual reality in cardiac rehabilitation: A systematic review and meta-analysis of randomized controlled trials. (September 2022) - Chen, Yanya; Cao, Li; Xu, Yinuo; Zhu, Mengdie; Guan, Bingsheng; Ming, Wai-kit
Abstract: Background: Cardiovascular disease has risen sharply and causes more premature deaths than cancer, while it represents a major economic burden for healthcare systems and impacts patients' quality of life negatively. Virtual reality has captured the attention of researchers in the field of cardiac rehabilitation. However, the efficacy of virtual reality among individuals undergoing cardiac rehabilitation remains inconclusive. Objective: To appraise research evidence on the effects of virtual reality for individuals undergoing cardiac rehabilitation. Design: Systematic review and meta-analysis. Methods: A systematic search of publications was conducted using Pubmed, Embase, Web of science, Cumulative Index to Nursing and Allied Health Literature database (CINAHL), Cochrane Central Register of Controlled trials and Physiotherapy Evidence Database (PEDro) from inception to 15 May 2022, without language restriction. The Cochrane Risk of Bias Tool was used to examine the methodological quality of the included randomized controlled studies. When feasible, a meta-analysis was performed to calculate the pooled effects using Review Manager (Version 5.4). Otherwise, narrative summaries were performed. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology was used to assess the certainty of the evidence. Results: A total of ten studies were included. Virtual reality probably increases exercise capacity for individuals undergoing cardiac rehabilitation (the pooled mean difference 49.55, 95% confidence interval 30.59 ~ 68.52, P  < 0.00001, moderate-certainty evidence) and might result in a reduction in emotional tension (mean difference − 6.43, 95% confidence interval − 9.02 ~ − 3.84, P  < 0.00001, low-certainty evidence) and intrapsychic stress (mean difference − 4.25, 95% confidence interval − 6.83 to − 1.67, P  = 0.001, low-certainty evidence). It also seemed to have a positive effect on quality of life, although meta-analysis could not be conducted to pool the results. Virtual reality might reduce depression (standardised mean difference − 0.48, 95% confidence interval − 0.84 ~ − 0.12, P  = 0.009, very low- certainty evidence), but the evidence was uncertain, with similar results of anxiety, general level of stress, external stress, total cholesterol, and low-density lipoprotein. The evidence was uncertain about the effect of virtual reality on high-density lipoprotein (mean difference − 1.79, 95% confidence interval − 8.96 ~ 5.38, P  = 0.62, very low-certainty evidence), with similar results of triglycerides and BMI. Conclusions: Individuals undergoing cardiac rehabilitation may benefit from virtual reality since it can improve exercise capacity and psychological outcomes. More large, and well-designed studies with tailored virtual reality intervention are warranted to confirm the effects of virtual reality on individuals undergoing cardiac rehabilitation. Tweetable abstract: Virtual reality may benefit individuals undergoing cardiac rehabilitation since it can improve exercise capacity and psychological outcomes.